ANALISIS DAYA SERAP LULUSAN AKADEMI KOMUNITAS SEMEN INDONESIA DI PERUSAHAAN GRESIK - Kholid Kholid (CAHAYA AKTIVA, 2018)
Semen Indonesia Community Academy is a newly established campus with the aim of preparing a Diploma workforce in two areas of offices and engineering in the surrounding companies. In fact, many companies do not know, so there is little opportunity to get employment opportunities. This study aims to obtain data on the number of companies that know the Semen Indonesia Community Academy and obtain data on the level of D2 workforce needs in the field of machinery and offices in the company.The research method used is a survey method with a descriptive model, using a nonprobability sample technique in the form of a purposive sample called the chosen sample. The sample chosen included companies in the district / sub-district around the campus, most of which were in the Districts of Kebomas and District of Manyar. Data collection using questionnaires and interviews were analyzed using the percentage descriptive analysis method, then processed with simple tabulations using Microsoft Excel, with tables and Diagram of Spider Webs.The results showed that most companies in Gresik (59%) did not know the Semen Indonesia Community Academy campus. Only a small number of companies in Gresik have D2 graduates (19%) and plan to accept D2 graduates (52%) who are still equal in high school / vocational high school.Based on the results of the study, it is expected that the Semen Indonesia Community Academy will increase the MoU / cooperation with as many companies as possible in order to establish apprenticeship communication and workforce needs for D2 graduates, because the company has never made a vacancy announcement for D2 graduates. returned to the D2 program at the Semen Indonesia Community Academy, considering that the highest demand for company employees from diploma graduates was D3 and D4 graduates. Likewise the government through the Ministry of Research, Technology and Higher Education and the Ministry of Manpower in order to better introduce the Indonesian National Qualifications Framework (KKNI) in all companies, especially graduates D1 and D2 so that the existence of the Community Academy can be recognized and get employment opportunities. Keywords: KKNI, Diploma